Cardiovascular risk factors of poor prognosis in COVID-19 – a review - Zaher, Eli A.; Keller, Daria M.; Suntharampillai , Nanthushan; Ujkani, Endrit; Lesiak, Maciej (Journal of Medical Science, 2021)
Since the first report in 2019, COVID-19 has claimed many lives, even those previously in good health. Therefore, a proper diagnosis and identification of patients at the highest risk of serious complications is vital. In fact, COVID-19 can lead to systemic inflammation and multiorgan dysfunction. Apart from the respiratory system, the circulatory system is also affected, including numerous complications due to the cytokine storm, direct cytotoxic effects, downregulation of angiotensin-converting enzyme 2, and low oxygen blood levels. In this review, we discussed cardiovascular risk factors associated with a poor prognosis in COVID-19 patients, including pre-existing risk factors or those acquired in the course of the infection. We also analyzed the role of biomarkers, ECG, and imaging in the identification of patients at the highest risk of unfavorable outcomes, as even subtle abnormalities in additional tests may have a significant impact on disease management.
Keywords: COVID-19; SARS-CoV-2; cardiovascular system; risk factors; poor prognosis